A robot arm-assisted acupuncture system with motion and force monitoring: establishment and validation - Li, Ying-Chen; Yu, Yi; Qiao, Xuan; Ren, Liu-Jie; Xu, Jing-Wen; Wang, Xin; Gu, Wei; Yao, Wei (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTraditional manual acupuncture faces challenges in quantifying stimulation parameters and preserving techniques consistency. This study presents a robot arm-assisted acupuncture system replicating manual manipulations with precise motion and force monitoring.MethodsSystem validation was conducted through a Laser Vibrometer to measure multiple frequency-amplitude combinations, followed by comparative analysis between robotic and manual acupuncture manipulations using both motion and force monitoring. Additionally, therapeutic efficacy was evaluated through an adjuvant arthritis rat model, comparing the analgesic effects between robotic and manual acupuncture at the Zusanli acupoint.ResultsThe Laser Vibrometer validation showed high precision, with mean absolute errors below 0.2 mm across all frequency-amplitude combinations. Comparative analysis demonstrated strong similarity between robotic and manual acupuncture in needle trajectories and force distributions, with Bhattacharyya coefficients of 0.9931 and 0.9976 for Lifting-Inserting and Mountain Burning manipulations. The robotic system achieved analgesic effects comparable to manual acupuncture, significantly improving pain thresholds over control groups.ConclusionThis work lays the groundwork for quantifiable, reproducible acupuncture therapy, driving the development of intelligent devices for standardized clinical applications.